Conservation of the HBV RNA element epsilon in nackednaviruses reveals ancient origin of protein-primed reverse transcription - Beck, Jürgen; Seitz, Stefan; Lauber, Chris; Nassal, Michael (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Hepadnaviruses, with the human hepatitis B virus as prototype, are small, enveloped hepatotropic DNA viruses which replicate by reverse transcription of an RNA intermediate. Replication is initiated by a unique protein-priming mechanism whereby a hydroxy amino acid side chain of the terminal protein (TP) domain of the viral polymerase (P) is extended into a short DNA oligonucleotide, which subsequently serves as primer for first-strand synthesis. A key component in the priming of reverse transcription is the viral RNA element epsilon, which contains the replication origin and serves as a template for DNA primer synthesis. Here, we show that recently discovered non-enveloped fish viruses, termed nackednaviruses [C. Lauber et al., Cell Host Microbe 22, 387-399 (2017)], employ a fundamentally similar replication mechanism despite their huge phylogenetic distance and major differences in genome organization and viral lifestyle. In vitro cross-priming studies revealed that few strategic nucleotide substitutions in epsilon enable site-specific protein priming by heterologous P proteins, demonstrating that epsilon is functionally conserved since the two virus families diverged more than 400 Mya. In addition, other cis elements crucial for the hepadnavirus-typical replication of pregenomic RNA into relaxed circular double-stranded DNA were identified at conserved positions in the nackednavirus genomes. Hence, the replication mode of both hepadnaviruses and nackednaviruses was already established in their Paleozoic common ancestor, making it a truly ancient and evolutionary robust principle of genome replication that is more widespread than previously thought.